Perceived Peer Victimization Predicts Anxiety Outcomes in a Prevention Program for Offspring of Anxious Parents. (21st December 2018) - Schleider, Jessica L.; Ginsburg, Golda S.; Drake, Kelly
Abstract : Offspring of anxious parents are at heightened risk for developing anxiety disorders. Preventive interventions for these youths are promising but not universally effective, creating a need to identify outcome predictors. Peer experiences (e.g., peer victimization, social support) are associated with youth anxiety trajectories but have been relatively unexplored in this context. Thus, this study tested whether peer experiences predicted anxiety-related outcomes in families participating in a randomized controlled trial of a child anxiety prevention program for families with a clinically anxious parent. Parental anxiety severity was also examined as a moderator of relations between peer experiences and subsequent child anxiety. Participants were 121 families (child M age = 8.69, 55.90% girls). Hierarchical logistic and linear regressions were used to test whether baseline peer-related factors predicted increased anxiety symptom severity and anxiety disorder onset over 12 months. Youths reporting greater perceived peer victimization at baseline were more likely to develop an anxiety disorder and had more severe anxiety symptoms 12 months later. Lower social support from classmates also predicted increased anxiety severity, but this effect became nonsignificant after accounting for peer victimization. Further, parental anxiety severity moderated the peer victimization–child anxiety severity link: Higher child-reported peer victimization predicted increased anxiety in offspring of highly and moderately anxious but not low anxious parents. Children's reports of peer victimization appear important for understanding which youth may not respond to preventive interventions in high-risk families—especially for children with more severely anxious parents. Implications for the focus of selective anxiety prevention programs are discussed.